2017
DOI: 10.1182/bloodadvances.2016004176
|View full text |Cite|
|
Sign up to set email alerts
|

Microenvironmental agonists generate de novo phenotypic resistance to combined ibrutinib plus venetoclax in CLL and MCL

Abstract: De novo resistance and rapid recurrence often characterize responses of B-cell malignancies to ibrutinib (IBR), indicating a need to develop drug combinations that block compensatory survival signaling and give deeper, more durable responses. To identify such combinations, we previously performed a combinatorial drug screen and identified the Bcl-2 inhibitor venetoclax (VEN) as a promising partner for combination with IBR in Mantle Cell Lymphoma (MCL). We have opened a multi-institutional clinical trial to tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 83 publications
8
77
0
Order By: Relevance
“…We provided the first evidence of the correlation of acquired TP53 and NSD2 gene mutations in progression and/or blastoid transformation in MCL on ibrutinib. Although our mutation results are from a small sample size and require further validation in large patient cohort, we believe that our data significantly add to the previous reports on ibrutinib resistance in MCL showing the role of the tumour microenvironment (Jayappa et al , ; Zhao et al , ), MAP3K14 alterations (Rahal et al , ) and mutations in chromatin modifier genes, such as NSD2 (Meissner et al , ), in MCL progression. One of the limitations of the mutation data reported in our study is due to the lack of matched germline samples for all samples, therefore the copy number data has a noisy background, especially the LOH calling, and therefore we focused on the deep deletions and high copy number gains, which had a high signal/noise ratio.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We provided the first evidence of the correlation of acquired TP53 and NSD2 gene mutations in progression and/or blastoid transformation in MCL on ibrutinib. Although our mutation results are from a small sample size and require further validation in large patient cohort, we believe that our data significantly add to the previous reports on ibrutinib resistance in MCL showing the role of the tumour microenvironment (Jayappa et al , ; Zhao et al , ), MAP3K14 alterations (Rahal et al , ) and mutations in chromatin modifier genes, such as NSD2 (Meissner et al , ), in MCL progression. One of the limitations of the mutation data reported in our study is due to the lack of matched germline samples for all samples, therefore the copy number data has a noisy background, especially the LOH calling, and therefore we focused on the deep deletions and high copy number gains, which had a high signal/noise ratio.…”
Section: Discussionsupporting
confidence: 68%
“…The mechanisms of ibrutinib resistance and the relevance of clonal evolution are being studied in B cell lymphoid malignancies (Burger et al , ; Jayappa et al , ; Landau et al , ; Zhao et al , ; Hershkovitz‐Rokah et al , ). In contrast to SLL/CLL, where the primary mode of ibrutinib resistance is considered to be via BTK C481S and PLCG2 gene mutations (Ahn et al , ; Woyach et al , ), studies in MCL (Chiron et al , ; Martin et al , ) and in follicular lymphoma (FL) (Jain et al , ) indicate that these mutations were uncommon in ibrutinib‐resistant patients.…”
mentioning
confidence: 99%
“…The authors suggested that CD40L protects cells from the effect of BTK inhibition and could have an important role in drug resistance pathways within the microenvironment. Supporting results were recently published by Jayappa et al () and are described below in the section relating to BCL2.…”
Section: The Effect Of the Microenvironment On Ibrutinib Resistancesupporting
confidence: 80%
“…Clinical trials assessing the safety and efficacy of ibrutinib + venetoclax in MCL (for example, NCT02419560 and NCT02471391) are ongoing. However, analysis of primary samples from patients with MCL and CLL revealed unexpected heterogeneous de novo resistance to this combination (Jayappa et al , ); the microenvironmental agonists IL10, CD40L and most potently, CpG‐oligodeoxynucleotides – a surrogate for unmethylated DNA and a specific agonist for TLR9 signalling – generated resistance to ibrutinib + venetoclax. Samples incubated with these agonists promoted NFkB activation, especially activation of the alternative pathway, leading to enhanced expression of the anti‐apoptotic proteins MCL1, BCL2L1 and survivin and decreasing BCL2 dependence.…”
Section: Overcoming Ibrutinib Resistancementioning
confidence: 99%
“…Venetoclax is an oral, highly selective BCL2 inhibitor with significant clinical efficacy in a range of B-cell lymphoproliferative disorders, including chronic lymphocytic leukaemia (CLL) (Roberts et al, 2016;Seymour et al, 2017), mantle cell lymphoma (MCL) , multiple myeloma (MM) (Moreau et al, 2017) and follicular lymphoma (FL) . Whilst various mechanisms of potential resistance to this targeted agent have been reported in model systems (Fresquet et al, 2014;Punnoose et al, 2016;Jayappa et al, 2017), to date only upregulation of BCL-xL (also termed BCL2L1) (Agarwal et al, 2019) or acquisition of a specific BCL2 mutation (Gly101Val) have been observed in samples from patients with progressive MCL or CLL respectively during therapy and confirmed as causing clinical resistance. Venetoclax monotherapy induces objective responses in 38% of patients with FL, including 14% complete responses .…”
mentioning
confidence: 99%